The Use of Multimedia Technology in English Language Teaching: A Global Perspective - Pun, Min (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
This paper aims to analyze the use of technology to English language teaching in the non-native speaking countries and to bring out the problems faced by both teachers and learners of English. The rapid development of science and technology such as multimedia technology has offered a better tool to explore the new teaching method. In fact, multimedia technology has played an important role in English language teaching, especially, in the non-native speaking of English situations. It also aims to make non-native speakers of English as language teachers aware of the strategies to use it in an effective manner. DOI: http://dx.doi.org/10.3126/ctbijis.v1i1.10466 Crossing the Border: International Journal of Interdisciplinary Studies Vol.1(1) 2013; 29-38